(untitled) (Heritage, 2025)
This paper discusses the first Spring Salons of Kosovo, which were organised in Priština during the 1970s. The Association of Fine Artists of Kosovo organised the Spring Salons. All members of the Association, both Serbs and Albanians, were eligible to participate. As an exhibition that established a tradition, the Spring Salon played a significant role in the development of fine arts in the province. At the first Spring Salons of the 1970s, Serbian artists became a minority, as Albanian artists were favoured and far more numerous.